Age‐related changes of shape and flow dynamics in healthy adult aortas: A 4D flow MRI study. Issue 1 (13th August 2018) - Callaghan, Fraser M.; Bannon, Paul; Barin, Edward; Celemajer, David; Jeremy, Richmond; Figtree, Gemma; Grieve, Stuart M.
Abstract : Background: Abnormal flow dynamics play an early and causative role in pathologic changes of the ascending aorta. Purpose: To identify: 1) the changes in flow, shape, and size that occur in the ascending aorta with normal human ageing and 2) the influence of these factors on aortic flow dynamics. Study Type: Retrospective. Subjects: In all, 247 subjects (age range 19–86 years, mean 49 ± 17.7, 169 males) free of aortic or aortic valve pathology were included in this study. Subjects were stratified by youngest (18–33 years; n  = 64), highest (>60 years, n  = 67), and the middle two quartiles (34–60 years, n  = 116). Field Strength/Sequence: Subjects underwent a cardiac MRI (3T) exam including 4D‐flow MRI of the aorta. Assessment: Aortic curvature, arch shape, ascending aortic angle, ascending aortic diameter, and the stroke volume normalized by the aortic volume (nSV) were measured. Velocity, vorticity, and helicity were quantified across the thoracic aorta. Statistical Tests: Univariate and multivariate regressions were used to quantify continuous relationships between variables. Results: Aortic diameter, ascending aortic angle, shape, and curvature all increased across age while nSV decreased (all P  < 0.0001). Systolic vorticity in the mid arch decreased by 50% across the age range ( P  < 0.0001), while peak helicity decreased by 80% ( P  < 0.0001). Curvature tightly governs optimal flow in the youngest quartile, with an effect size 1.5 to 4 times larger than other parameters in the descending aorta, but had a minimal influence with advancing age. In the upper quartile of age, flow dynamics were almost completely determined by nSV, exerting an effect size on velocity and vorticity >10 times that of diameter and other shape factors. Data Conclusion: Aortic shape influences flow dynamics in younger subjects. Flow conditions become increasingly disturbed with advancing age, and in these conditions nSV has a more dominant effect on flow patterns than shape factors. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:90–100.